A Study on Relationship Between Knowledge Management and Occupational Stress - GOPINATH, DR.R.; CHITRA, DR.A.; KALPANA, DR.R. (The journal of contemporary issues in business and government, 2021)
Background: In today’s scenario every individual is multi-faceted, the number of dimensions has increased comparatively. But they are not different in each dimension, they are the same. This conflict and contradiction in role playing have made them though, and the requirement of perfectionism in every role has imposing lot of pressure on them, which pave ways to Occupational Stress. Every face of an individual demands a unique set of knowledge to perform the task and being good in doing that. This paper is an attempt whether acquisition and management of knowledge has any relationship with the stress caused by work and either the Occupational Stress has influenced by the Knowledge Management or not. Methodology: The population of the study includes the total selected faculty members of state university (N=412) out of them 180 were selected as samples using random sampling technique. Knowledge Management Survey and Occupational Stress Questionnaire developed by England Institute of Health and Safety were used to collect the primary data. Findings: The results of correlation and regression analysis explain a positive relationship and significant influence of Knowledge Management on Occupational Stress. Conclusion: It can be concluded that faculties’ apprehension of enhancement of Knowledge Management increases their level of Occupational Stress.